(untitled) (International Journal of Statistical Sciences, 2024)
Nutrition is a basic need of human life and a prerequisite for a healthy life, good health of children is very important for future development of the country. This paper examines the nutritional status of under-five children in India. A total number of 168942 under-five children in India have been considered in the sample for the study. The data has been taken from the fifth national family health survey of 2019-21, India. Children who fall below –2SD from the median of the respective Z-scores of ‘weight for age’ (WAZ), ‘height for age’ (HAZ) and ‘weight for height’ (WHZ) are considered as underweight, stunted and wasted respectively. Prevalence of underweight, stunted and wasted children are 29.2%, 35.4% and 18.7% respectively and boys were more prevalent than girls. Also, child undernutrition tends to decrease with the mother’s level of education, the mother’s health status, and the wealth index of the family. Child’s health is also directly related with oropharyngeal administration of colostrum to baby. The results show that the mean values of height and weight steadily increase all along the ages up to 59 months. Growth patterns and the prevalence of undernutrition are almost the same among girls and boys. The prevalence of undernutrition (WAZ and HAZ) increases up to the child’s age group of 12-23 months, and then decreases slightly thereafter or remains more or less same, but for WHZ it decreases throughout. It is seen from our study that in both the sexes of under-five children, underweight is directly and wasting is indirectly related with the ages, but no clear association is seen in stunting. The study also points out the necessity of improving mothers’ education, awareness of health, in addition to the economic condition of the families, to overcome the undernutrition of under-five children. IJSS, Vol. 24(2)s (Special Issue), December, 2024, pp 137-148